2014
DOI: 10.12707/riii1393
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and stress in the preoperative surgical patient

Abstract: Enquadramento: A ansiedade, a depressão e o stresse são comuns nos doentes durante o internamento, pelo que continua a revelar-se pertinente a sua avaliação em diferentes contextos de saúde. Objetivos: Identificar os níveis de ansiedade, de depressão e de stresse no pré-operatório do doente cirúrgico e analisar a sua associação com algumas variáveis sociodemográficas e clínicas. Metodologia: Estudo descritivo e correlacional, numa amostra de 100 doentes, no dia anterior à cirurgia, utilizando um questionário d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 6 publications
3
14
0
12
Order By: Relevance
“…This study did not prove that the pre-surgery education does not give a positive effect, but it has been analyzed that the education given before going in for surgery does not affect anxiety and depression (Isher, 2010). A significant level of depression statistically is found in pre-surgery patients in accordance with the level of educational qualification and length of staying in the hospital (Dos Santos, et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
See 4 more Smart Citations
“…This study did not prove that the pre-surgery education does not give a positive effect, but it has been analyzed that the education given before going in for surgery does not affect anxiety and depression (Isher, 2010). A significant level of depression statistically is found in pre-surgery patients in accordance with the level of educational qualification and length of staying in the hospital (Dos Santos, et al, 2014).…”
Section: Discussionmentioning
confidence: 73%
“…According to the research of Dos Santos, et al (2014), after testing various hypotheses based on the different socio-demographic variables, the results showed that there was no significant difference statistically in the levels of anxiety, depression, and stress in a pre-surgery surgical patient according to gender, age, marital status, and profession. These results are also consistent with the results of a research done by Marcolino, et al (2017), which aimed to understand the effects of social demographic variables of gender, age, marital status and education about anxiety and depression, concluded that there was no significant difference in the level of depression and anxiety (Dos Santos, et al, 2014). Komolafe and Csernus (2015), stated that feelings of patient anxiety did not correlate with factors of marital status, religiosity and whether patients had had previous surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations